(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Tourism is an activity which includes travelling and staying in places that are outside of their location for business, vacation and other purposes. The present paper gives an account of a tourism in regard to eco tourism and religious tourism. The prime objective is to bring out the tourism possibilities and challenges of tourism in the state of Asaam. The paper is based on both primary and secondary data. Efforts are being made to take the benefits and different aspects of tourism problems and protentiatials of Eco-Tourism and Religious Tourism in Assam.